Rice Genotype Differences in Tolerance of Zinc-Deficient Soils: Evidence for the Importance of Root-Induced Changes in the Rhizosphere - Mori, Asako; Kirk, Guy J. D.; Lee, Jae-Sung; Morete, Mark J.; Nanda, Amrit K.; Johnson-Beebout, Sarah E.; Wissuwa, Matthias (Frontiers in Plant Science, 2016)
Zinc (Zn) deficiency is a major constraint to rice production and Zn is also often deficient in humans with rice-based diets. Efforts to breed more Zn-efficient rice are constrained by poor understanding of the mechanisms of tolerance to deficiency. Here we assess the contributions of root growth and root Zn uptake efficiency, and we seek to explain the results in terms of specific mechanisms. We made a field experiment in a highly Zn-deficient rice soil in the Philippines with deficiency-tolerant and -sensitive genotypes, and measured growth, Zn uptake and root development. We also measured the effect of planting density. Tolerant genotypes produced more crown roots per plant and had greater uptake rates per unit root surface area; the latter was at least as important as root number to overall tolerance. Tolerant and sensitive genotypes took up more Zn per plant at greater planting densities. The greater uptake per unit root surface area, and the planting density effect can only be explained by root-induced changes in the rhizosphere, either solubilizing Zn or neutralizing a toxin that impedes Zn uptake (possibly HCO3- or Fe2+), or both. Traits for these and crown root number are potential breeding targets.